Confirmatory diagnosis of African swine fever in southern Nigeria by immunoblotting assay (2005)
When a swine epizootic occurred in groups of pigs in south western Nigeria in 2001, a need for detailed investigation and confirmatory diagnosis arose at the University of Ibadan. A class of epizootiology students at the university was involved in the investigation. Comprehensive information about the nature and causation of the disease was provided. Four diagnostic techniques were used for confirmatory diagnosis, including Indirect Enzyme Linked Immunosorbent Assay (I-ELISA), immunoblotting, polymerase chain reaction (PCR), and virus isolation. Only immunoblotting assay was used at the University of Ibadan, while samples were sent to the National Veterinary Research Institute (NVRI) in Vom, Nigeria for I-ELISA and to two reference laboratories for African swine fever in South Africa and Madrid, Spain for PCR and virus isolation respectively. The results obtained from these laboratories using the other three diagnostic techniques were compared with that of the immunoblotting assay. Immunoblotting assay confirmed all samples that tested positive on PCR and virus isolation. It was also relatively easier to use, highly sensitive and specific for confirmatory diagnosis. It was however costlier in application for large sample size testing compared to I-ELISA.